SNRNP200 Mutations Cause Autosomal Dominant Retinitis Pigmentosa - Zhang, Tao; Bai, Jingshan; Zhang, Xinyi; Zheng, Xiaowei; Lu, Nan; Liang, Zhongyin; Lin, Ling; Chen, Yongsong (Frontiers in Medicine, 2021)
The small nuclear ribonucleoprotein 200 kDa (SNRNP200) gene plays a key role in the maturation of pre-message RNA (pre-mRNA) splicing with the indication for the etiology of retinitis pigmentosa (RP). Gene recognition can facilitate the diagnosis of these patients for better clinical management, treatment and counseling. This study aimed to outline the causative mutation in a Chinese family and the pathogenic mechanism of this SNRNP200 mutation in RP. Eighteen individuals from the affected family underwent a complete ophthalmic examination. Whole exome sequencing (WES) was conducted to identify the pathogenic variant in the proband, which was then confirmed by Sanger sequencing. Expression of the SNRNP200 transcript in zebrafish was identified via whole mount in situ hybridization. Morpholino oligonucleotide (MO) and SNRNP200 wild and mutant mRNA were injected into zebrafish embryos followed by analyses of the systemic changes and retinal phenotypes using immunofluorescence. Heterozygous SNRNP200c.C6088T (p.Arg2030Cys) mutation was ascertained in two members of this family: the proband and his father (II-2). Overexpression of SNRNP200Arg2030Cys, but not SNRNP200WT caused systemic deformities in the wild-type zebrafish embryos with the retina primarily injured, and significantly increased death rates in the morphant embryos, in which the orthologous zebrafish SNRNP200 gene was blocked. In conclusion, this study reports a novel heterozygous SNRNP200c.C6088T mutation, which is evidenced to cause RP via a dominant-negative effect.